Rare earth element doped multiphase continuous silicon carbide ceramic fiber and preparation method thereof

By introducing rare earth elements and boron elements into silicon carbide fibers and optimizing the grain boundary structure, the problem of insufficient temperature resistance and oxidation resistance at high temperatures is solved, and high-performance silicon carbide ceramic fibers are realized, with excellent Mechanical properties and low cost characteristics.

CN119285361APending Publication Date: 2025-01-10GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202411485015.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing silicon carbide fibers have problems with insufficient temperature resistance and oxidation resistance at high temperatures, especially due to the influence of free carbon at grain boundaries, the fiber's temperature resistance and oxidation resistance need to be improved.

Method used

The preparation method of rare earth element doped complex phase continuous silicon carbide ceramic fiber is adopted, and the rare earth element and boron element are introduced through ceramic pioneer synthesis, melt spinning, air cross-linking and high-temperature ceramicization to optimize the grain boundary structure and sintering performance of the fiber. , and a high melting point ceramic phase is added to the fibers to inhibit grain growth and slippage.

Benefits of technology

It significantly improves the temperature resistance, oxidation resistance and creep resistance of the fiber, reduces the preparation cost, and obtains excellent mechanical properties. The single filament strength reaches 1.8-3.5GPa, and the Young's modulus reaches 350-410GPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285361A_ABST
    Figure CN119285361A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth element doped multiphase continuous silicon carbide ceramic fiber and a preparation method thereof.The preparation method comprises the steps of ceramic precursor preparation, melt spinning, air crosslinking, pyrolysis inorganic treatment and high-temperature ceramization. In the preparation method, heterogeneous metal elements, rare earth elements and boron elements are introduced through precursor synthesis; by combining air crosslinking, the sintering performance in the fiber is improved, the content of free carbon in the fiber is reduced, and the grain boundary composition and structure of the silicon carbide ceramic fiber are optimized. The prepared rare earth doped metal boride-containing multiphase silicon carbide ceramic fiber has excellent mechanical properties, high temperature resistance and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon carbide ceramic fibers, and in particular to a rare earth element doped multiphase continuous silicon carbide ceramic fiber and a preparation method thereof. Background Art

[0002] Silicon carbide fiber reinforced ceramic matrix composites have the excellent characteristics of low density, high temperature resistance, oxidation resistance and corrosion resistance, and are known as the most promising candidate materials for the next generation of aircraft engines. As the reinforcing phase material of ceramic matrix composites, the temperature resistance and oxidation resistance of silicon carbide fiber directly determine the preparation and use temperature of ceramic matrix composites.

[0003] The preparation methods of silicon carbide fibers include chemical vapor deposition (CVD), activated carbon fiber sintering, micropowder sintering and precursor conversion. The precursor conversion method has the characteristics of molecular design of the precursor, low ceramic temperature, easy introduction of heterogeneous elements and low preparation temperature. It is the most important preparation method for silicon carbide fibers.

[0004] At present, three generations of silicon carbide fibers have been developed at home and abroad. The first generation of silicon carbide fibers is represented by Nicalon fibers, which are mainly made of SiC x O y The fiber is composed of amorphous phase, nano-SiC crystallites and free carbon. The operating temperature of the fiber is only 1000℃. Above 1000℃, SiC x O y The amorphous phase decomposes, releasing SiO and CO gases, and the mechanical properties of the fiber decrease significantly.

[0005] The second generation of silicon carbide fiber is represented by Hi-Nicalon fiber, which uses electron beam cross-linking during the fiber infusibility treatment stage to reduce the introduction of oxygen elements. Hi-Nicalon fiber is composed of nano-scale SiC grains, free carbon and a small amount of SiC x O y Phase composition. SiC x O y The reduction of phase increases the use temperature of the second-generation silicon carbide fiber, and the fiber can still maintain good mechanical properties at 1250°C. However, due to the presence of a large amount of free carbon at the SiC grain boundary, the oxidation resistance of silicon carbide fiber needs to be further improved.

[0006] On the basis of electron beam crosslinking, H2 is introduced in the pyrolysis process to remove the free carbon in the fiber, and a nearly stoichiometric silicon carbide fiber is prepared (represented by Hi-Nicalon S fiber abroad and KD-S and Cansas 3303 in China), and the heat resistance and oxidation resistance of the fiber are further improved. In addition, Al is introduced into the fiber as a sintering aid, and SiC is used in the high-temperature ceramic stage.x O y Phase decomposition releases CO, reducing the free carbon in the ceramic fiber, and further high-temperature sintering of Al to prepare sintered silicon carbide fiber (represented by Tyranno SA abroad and KD-SA in China).

[0007] Although the current third-generation silicon carbide fiber is close to the stoichiometric ratio of SiC, there is still a small amount of free carbon at the grain boundaries of silicon carbide, which will still affect the temperature resistance and oxidation resistance of silicon carbide fibers.

[0008] Therefore, how to develop a silicon carbide fiber with excellent temperature resistance and oxidation resistance and a preparation method thereof has become a problem that needs to be solved urgently. Summary of the invention

[0009] In order to solve the above technical problems, the purpose of the present invention is to provide a rare earth element doped multiphase continuous silicon carbide ceramic fiber and a preparation method thereof. The present invention prepares the rare earth element doped multiphase continuous silicon carbide ceramic fiber through ceramic precursor preparation, melt spinning, air crosslinking, pyrolysis inorganicization and high-temperature ceramicization in sequence, and the preparation cost is low. The rare earth element doped multiphase continuous silicon carbide ceramic fiber has excellent temperature resistance and antioxidant properties.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a rare earth element-doped multiphase continuous silicon carbide ceramic fiber, the preparation method comprising:

[0012] (1) mixing polycarbosilane, a metallocene compound, a rare earth compound and a boron-containing compound, reacting the mixture under high temperature and high pressure to obtain an intermediate product, and dissolving, filtering and distilling the intermediate product to obtain a polymetallic borocarbosilane ceramic precursor containing a rare earth element;

[0013] (2) preparing fiber precursors by melt spinning the rare earth element-containing polymetallic borocarbosilane ceramic precursor described in step (1);

[0014] (3) cross-linking the fiber precursors described in step (2) in a synthetic air atmosphere to prepare cross-linked fibers;

[0015] (4) In an inert atmosphere and / or a reducing atmosphere, heating and pyrolyzing the crosslinked fibers in step (3) to obtain Si-MCOB-RE inorganic fibers, wherein M represents a metal element and RE represents a rare earth element;

[0016] (5) Under an inert atmosphere, sintering the Si-MCOB-RE inorganic fiber in step (4) at a high temperature to obtain the rare earth element doped multiphase continuous silicon carbide ceramic fiber.

[0017] In the preparation method of the present invention, heterogeneous metal elements, rare earth elements and boron elements are introduced through precursor synthesis, combined with air crosslinking, so as to improve the sintering performance inside the fiber, reduce the free carbon content inside the fiber, optimize the grain boundary composition and structure of the silicon carbide ceramic fiber, and compared with the existing silicon carbide fibers, the temperature resistance, oxidation resistance and creep resistance of the rare earth-doped metal boride-containing composite silicon carbide ceramic fibers are improved.

[0018] The present invention adds a high melting point and high thermal stability ceramic phase MB2 (M=Ti, Zr, Hf) at the SiC grain boundary of the silicon carbide fiber, which is beneficial to optimizing the grain boundary structure of the silicon carbide fiber, effectively inhibiting the grain growth of silicon carbide and the sliding of silicon carbide grains along the grain boundary, thereby improving the temperature resistance and high-temperature creep resistance of the silicon carbide fiber.

[0019] The inventors also found that in addition to introducing high melting point ceramic phases at the grain boundaries, doping a small amount of rare earth elements in the fiber can further improve the high temperature performance of the fiber. On the one hand, by introducing rare earth elements, it can further promote sintering and improve the sintering performance of the fiber, especially the fiber core. For example, rare earth oxide Y2O3 is a common sintering aid for SiC ceramics, and SiC ceramics with a high degree of densification can be obtained through liquid phase sintering.

[0020] On the other hand, since SiC and MB2 phases will be oxidized into SiO2 and MO2 phases during the high-temperature oxidation process, the crystallized MO2 phase changes during the heating and cooling process, causing volume changes, resulting in a decrease in fiber performance. The introduction of rare earth elements can also stabilize the MO2 phase and improve the high-temperature oxidation resistance of the fiber. For example, ZrO2, as a thermal barrier coating material, undergoes a phase transition from tetragonal phase to monoclinic phase when the temperature drops to around 1100°C, and the volume expands by 3%-5%. This volume effect causes stress and cracks in the oxide layer. The YSZ coating prepared by adding 6-8wt% Y to ZrO2 has a more stable phase structure and improves the thermal stability of the coating.

[0021] In addition, the diffusion rate of oxygen atoms in the oxidation protective layer SiO2 glass is inversely proportional to the viscosity. The higher the oxidation temperature, the lower the viscosity of the SiO2 glass, and the weaker the protective effect on the fiber. 3+ ), can increase the viscosity of SiO2 glass and further enhance the oxidation resistance of SiC ceramics. 3+ Medium 3+ With the smallest ionic radius, Yb2Si2O7 is more easily diffused into SiO2 glass to form Yb2Si2O7, slowing down the inward diffusion rate of oxygen atoms. 3+It is a high-field strength, high-charge ion that can stabilize the oxygen atoms on the SiO2 glass network structure, thereby inhibiting the breakage of Si-O bonds at high temperatures, slowing down the high-temperature volatilization and decomposition of SiO2 glass, and effectively increasing the oxidation resistance temperature of SiC ceramics.

[0022] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0023] Preferably, the polycarbosilane structural formula in step (1) is:

[0024]

[0025] Wherein, m is an integer equal to or greater than 3, for example, it can be 3, 5, 10, 15 or 30, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; n is an integer equal to or greater than 0, for example, it can be 0, 5, 7, 10 or 35, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0026] Preferably, the softening point temperature of the polycarbosilane is 70-150°C, for example, it can be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] The present invention uses polycarbosilane with a low softening point as a raw material. Such polycarbosilane generally has a lower molecular weight, a simpler structure and a higher reactivity. By controlling the reaction temperature and time, a ceramic precursor with a suitable softening point, excellent rheological properties and spinning properties can be obtained. If the present invention uses polycarbosilane with a softening point temperature higher than 150°C as a raw material, the reaction conditions are difficult to control, the molecular weight of the synthesized precursor is too high, the spinning performance is affected, and ultimately a continuous SiC fiber with good mechanical properties cannot be obtained.

[0028] Preferably, the metallocene compound comprises any one of dichlorotitanocene, dichlorozirconocene or dichlorohafnocene, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of dichlorotitanocene and dichlorozirconocene, a combination of dichlorozirconocene and dichlorohafnocene, a combination of dichlorotitanocene and dichlorohafnocene, or a combination of dichlorotitanocene, dichlorozirconocene and dichlorohafnocene.

[0029] Preferably, the rare earth compound comprises any one of acetylacetone compounds, isopropanol compounds, and heptanedione compounds of rare earth elements, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of acetylacetone compounds and isopropanol compounds, a combination of isopropanol compounds and heptanedione compounds, a combination of acetylacetone compounds and heptanedione compounds, or a combination of acetylacetone compounds, isopropanol compounds, and heptanedione compounds.

[0030] Preferably, the rare earth element includes any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium or yttrium, or a combination of at least two thereof, preferably ytterbium and / or yttrium.

[0031] Preferably, the boron-containing compound comprises any one of borane, boron trichloride and cycloborazine or a combination of at least two thereof. Typical but non-limiting combinations include a combination of borane and boron trichloride, a combination of boron trichloride and cycloborazine, a combination of borane and cycloborazine, or a combination of borane, boron trichloride and cycloborazine.

[0032] Preferably, the structural formula of the borazine is:

[0033]

[0034] Wherein, m is an integer equal to or greater than 1, for example, 1, 10, 20, 30 or 40, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, and R is at least one of CH3, H or Cl.

[0035] Preferably, the mass ratio of the polycarbosilane, the metallocene compound, the rare earth compound and the boron-containing compound in step (1) is (100-120):(5-15):(1-6):(5-10), for example, it can be 100:5:1:5, 100:5:3:5, 100:5:5:5, 100:5:7:5, 100:5:9:5, 110:5:1:5, 120:5:3:5, 110:5:5:5, 120:5:6:5, 110:5:5:5, 100:6:1:5, 100:8:3:5, 100:10:6:5, 100:5:6:7, 100:5:4:9 or 100:5:3:10, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] The present invention adopts low-softening-point polycarbosilane as a raw material, and adjusts the element content of the precursor by controlling the ratio of the low-softening-point polycarbosilane, the metallocene compound, the rare earth compound and the boron-containing compound, so that the content of the metal element in the precursor is 0.1-5wt%, the content of the rare earth element Y is 0.1-1wt%, the content of the rare earth element Yb is 0.1-1wt%, and the content of the B element is 0.1-4.0wt%.

[0037] The present invention controls the contents of metal elements, rare earth elements and B elements to 0.1-5wt%, 0.1-1wt% and 0.1-4.0wt% respectively, in order to avoid generating too much second phase between SiC grains, hindering the uniform growth of SiC grains and the bonding between each other during high-temperature sintering, resulting in loose and porous SiC fiber structure, reduced mechanical properties and anti-oxidation properties.

[0038] Preferably, the temperature of the high temperature and high pressure reaction is 250-400°C, for example, it can be 250°C, 270°C, 290°C, 300°C, 320°C, 340°C, 350°C, 370°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] The present invention further controls the temperature of the high temperature and high pressure reaction to be 250-400°C, which is lower than the reaction temperature in the prior art. If the reaction temperature is too high, it will cause excessive cross-linking reaction of the raw material molecules to generate a ceramic precursor with too large a molecular weight and poor spinnability; if the reaction temperature is too low, it will reduce the reaction degree and raw material utilization rate.

[0040] Preferably, the pressure of the high temperature and high pressure reaction is 1.0-5.0 MPa, for example, 1.0 MPa, 2.0 MPa, 3.0 MPa, 4.0 MPa or 5.0 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the high temperature and high pressure reaction time is 4-12 hours, for example, it can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the melt spinning step in step (2) specifically comprises: adding a polymetallic borocarbosilane ceramic precursor containing rare earth elements into a spinning tank, and performing melt spinning after high-temperature degassing and cooling to prepare fiber precursors.

[0043] The present invention controls the composition of the precursor, the temperature of air crosslinking and the holding time, thereby controlling the reaction degree of Si-H, metallocene and O2 of the polycarbosilane to form an insoluble and infusible spatial network structure, so that the B content of the inorganic fiber obtained after the pyrolysis in step (4) is controlled at 0.1-4.0wt%, and the oxygen content is stably controlled at 5.0-11.0wt%.

[0044] Preferably, the high-temperature degassing temperature is 320-370°C, for example, it can be 320°C, 330°C, 340°C, 350°C, 360°C or 370°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the high-temperature degassing time is 2-4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the melt spinning temperature is 90-130° C. higher than the softening point of the polymetallic borocarbosilane ceramic precursor.

[0047] Preferably, the melt spinning temperature is 290-340°C, for example, 290°C, 300°C, 310°C, 320°C, 330°C or 340°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the pressure during melt spinning is 0.05-0.5 MPa, for example, it can be 0.05 MPa, 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa or 0.5 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the diameter of the fiber filament is 12-20 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the temperature of the cross-linking reaction in step (3) is 160-250°C, for example, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0051] Preferably, the synthetic air is composed of 21% high-purity oxygen and 79% high-purity nitrogen.

[0052] Preferably, the heating rate of the cross-linking reaction is 0.5-5°C / min, for example, it can be 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the insulation time of the cross-linking reaction is 0.5-10 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the temperature of the pyrolysis in step (4) is 1000-1300°C, for example, it can be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0055] Preferably, the heating rate of the pyrolysis is 0.5-5°C / min, for example, it can be 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] Preferably, the heating pyrolysis time is 0.5-3h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the inert gas includes high-purity nitrogen or high-purity argon.

[0058] Preferably, the reducing atmosphere comprises a mixture of nitrogen and hydrogen with a concentration of 2-10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the hydrogen mixture is a mixture of nitrogen and hydrogen with a mass fraction of 0.1-50%, for example, it can be 0.1%, 0.3%, 0.5%, 1%, 10%, 20%, 30%, 40% or 50%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] Preferably, the high temperature sintering temperature in step (5) is 1800-1950°C, for example, 1800°C, 1850°C, 1900°C or 1950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0061] Preferably, the high temperature sintering time is 0.1-3 h, for example, it can be 0.1 h, 0.5 h, 0.8 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] Preferably, the inert gas comprises high-purity argon.

[0063] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0064] (1) adding polycarbosilane, metallocene compound, rare earth compound and boron-containing compound into a high-pressure reactor in a mass ratio of (100-120):(5-15):(1-6):(5-10), carrying out a high-temperature and high-pressure reaction for 4-12 hours at a temperature of 250-400° C. and a pressure of 1.0-5.0 MPa to obtain an intermediate product, dissolving the intermediate product in xylene, filtering and distilling under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements;

[0065] (2) adding the rare earth element-containing polymetallic borocarbosilane ceramic precursor described in step (1) into a spinning tank, maintaining the temperature at 320-370° C. for 2-4 h for degassing, then cooling to 290-340° C., and performing melt spinning at a pressure of 0.05-0.5 MPa to prepare fiber precursors with a diameter of 12-20 μm;

[0066] (3) heating the fiber precursor described in step (2) to 160-250° C. at a heating rate of 0.5-5° C. / min in a synthetic air atmosphere and keeping the temperature for 0.5-10 h to prepare a cross-linked fiber;

[0067] (4) heating the cross-linked fiber in step (3) to 1000-1300° C. at a heating rate of 0.5-5° C. / min in an atmosphere of high-purity nitrogen or high-purity argon or a mixture of nitrogen and 2-10% hydrogen for 0.5-3 h to obtain Si-MCOB-RE inorganic fiber;

[0068] (5) Sintering the Si-MCOB-RE inorganic fiber in step (4) in high-purity argon at 1800-1950° C. for 0.1-3 h to obtain the rare earth element-doped multiphase continuous silicon carbide ceramic fiber.

[0069] In a second aspect, the present invention provides a rare earth element doped multi-phase continuous silicon carbide ceramic fiber, wherein the rare earth element doped multi-phase continuous silicon carbide ceramic fiber is prepared according to the preparation method described in the first aspect.

[0070] The rare earth element doped multiphase continuous silicon carbide ceramic fiber prepared by the invention has excellent mechanical properties.

[0071] Preferably, the rare earth element doped multiphase continuous silicon carbide ceramic fiber has a single filament strength of 1.8-3.5 GPa and a Young's modulus of 350-410 GPa.

[0072] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0073] Compared with the prior art, the present invention has at least the following beneficial effects:

[0074] (1) In the precursor synthesis stage, the present invention introduces heterogeneous metal elements, rare earth elements and boron elements into polycarbosilane by chemically reacting low-softening-point polycarbosilane with metallocene compounds, rare earth compounds and boron-containing compounds. The introduced elements can be mixed evenly at the atomic scale, thereby avoiding segregation or enrichment of the heterogeneous elements introduced in the fiber during subsequent operations.

[0075] (2) The present invention adopts air crosslinking in the infusible stage of the fiber, avoiding the use of expensive electron beam crosslinking, reducing the preparation cost of the fiber, avoiding the use of nitrogen oxide atmosphere crosslinking, and reducing corrosion to equipment and environmental impact.

[0076] (3) The present invention can introduce an inert atmosphere or a reducing atmosphere during the fiber pyrolysis inorganic stage, and can adjust the concentration of hydrogen during the pyrolysis process according to the oxygen content introduced by air cross-linking, thereby regulating the carbon content in the inorganic fiber and ceramic fiber. Compared with the existing process, the process conditions are broadened and more conducive to industrial production.

[0077] (4) The rare earth element doped composite continuous silicon carbide ceramic fiber prepared by the technology of the present invention has a single filament strength of 1.8-3.5 GPa and a Young's modulus of 350-410 GPa, and has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 is a scanning electron microscope image of a cross section of a rare earth element-doped multiphase continuous silicon carbide ceramic fiber prepared in Example 1 of the present invention;

[0079] Figure 2is an X-ray diffraction spectrum of a cross section of a rare earth element-doped multiphase continuous silicon carbide ceramic fiber prepared in Example 1 of the present invention;

[0080] Figure 3 This is an X-ray energy spectrum scanning image of the rare earth element doped multiphase continuous silicon carbide ceramic fiber prepared in Example 4 of the present invention;

[0081] Figure 4 This is an X-ray energy spectrum scanning image of the rare earth element doped multiphase continuous silicon carbide ceramic fiber prepared in Example 5 of the present invention;

[0082] Figure 5 It is a scanning electron microscope picture of the cross section of the ceramic fiber prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0083] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0084] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.

[0085] Example 1

[0086] This embodiment provides a method for preparing rare earth element doped multi-phase continuous silicon carbide ceramic fiber, the preparation method comprising:

[0087] (1) Polycarbosilane with a softening point of 70°C, zirconocene dichloride, yttrium heptanedione, ytterbium heptanedione and trichloroborazine are placed in an autoclave in a mass ratio of 100:10:2:1:5, the temperature is raised to 340°C, the pressure is raised to 3.0 MPa, and the reaction is carried out at high temperature and high pressure for 6 hours, then cooled to room temperature, and the prepared precursor is dissolved and filtered with xylene, and then distilled under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements.

[0088] (2) The prepared polymetallic borocarbon silane ceramic precursor containing rare earth elements was added into a spinning tank and kept at 350°C for 3 hours for degassing treatment. The temperature was then lowered to 310°C and the pressure was 0.1 MPa for melt spinning to prepare fiber precursors with an average diameter of 16 μm.

[0089] (3) The fiber precursor was placed in a tubular furnace, and the vacuum was evacuated to replace the nitrogen three times. Synthetic air was introduced at a flow rate of 1 L / min, and the temperature was increased to 160°C at a heating rate of 1°C / min. The temperature was kept at this temperature for 10 h, and then the temperature was lowered to room temperature to obtain cross-linked fibers.

[0090] (4) The cross-linked fibers were placed in a tubular furnace, and the argon gas was replaced by vacuum three times. The pyrolysis reaction was carried out at a heating rate of 2°C / min. The temperature was raised to 1000°C and kept for 3 hours, and then cooled to room temperature to obtain inorganic fibers.

[0091] (5) placing the inorganic fiber in a high-temperature graphite furnace, evacuating and replacing argon gas three times, sintering at a high temperature of 1800° C. at a heating rate of 5° C. / min for 3 h, and cooling to room temperature to obtain the rare earth element-doped composite continuous silicon carbide ceramic fiber.

[0092] The composition and structure of the inorganic fiber obtained in step (4) of Example 1 and the rare earth element doped multiphase continuous silicon carbide ceramic fiber obtained in step (5) were tested respectively. The oxygen content of the inorganic fiber was measured to be 9.8% by nitrogen oxygen analyzer, the oxygen content of the rare earth element doped multiphase continuous silicon carbide ceramic fiber was 0.3wt%, the carbon content of the rare earth element doped multiphase continuous silicon carbide ceramic fiber was measured to be 30.1wt% by carbon sulfur analyzer, and the element contents of Zr, B, Y, and Yb in the rare earth element doped multiphase continuous silicon carbide ceramic fiber were measured to be 1.4wt%, 0.8wt%, 0.4wt%, and 0.3wt%, respectively, by inductively coupled plasma emission spectroscopy.

[0093] The SEM image of the prepared rare earth element doped composite continuous silicon carbide ceramic fiber is shown in Figure 1 As shown, from Figure 1 It can be seen that the fibers are in an obvious crystalline state with a dense structure, and no obvious holes are observed from the core to the surface.

[0094] The XRD pattern of the prepared rare earth element doped composite continuous silicon carbide ceramic fiber is shown in Figure 2 As shown, from Figure 2 It can be seen that the main phase is SiC and ZrB2 ceramic phase. Due to the low content of elements Y and Yb, no corresponding diffraction peaks appear in the XRD spectrum. The grain size of SiC is 38nm and the grain size of ZrB2 is 32nm calculated by Scherrer formula.

[0095] Example 2

[0096] This embodiment provides a method for preparing rare earth element doped multi-phase continuous silicon carbide ceramic fibers, the preparation method comprising:

[0097] (1) Polycarbosilane with a softening point of 150°C, dichlorotitanocene, yttrium heptanedione, ytterbium heptanedione and trichloroborazine are placed in an autoclave in a mass ratio of 100:15:4:2:5, the temperature is raised to 250°C, the pressure is raised to 1.0 MPa, and the reaction is carried out at high temperature and high pressure for 4 hours, then the temperature is lowered to room temperature, the prepared precursor is dissolved in xylene, filtered, and then distilled under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements.

[0098] (2) The prepared polymetallic borocarbosilane ceramic precursor containing rare earth elements was added into a spinning tank and kept at 370°C for 4 hours for degassing treatment. The temperature was then lowered to 340°C and the pressure was 0.5 MPa for melt spinning to prepare fiber precursors with an average diameter of 18 μm.

[0099] (3) The fiber precursor was placed in a tubular furnace, and the vacuum was evacuated and replaced with nitrogen three times. Synthetic air was introduced at a flow rate of 1 L / min, and the temperature was increased to 250°C at a heating rate of 0.5°C / min. The temperature was kept at this temperature for 0.5 h, and then cooled to room temperature to obtain cross-linked fibers.

[0100] (4) The cross-linked fibers were placed in a tubular furnace, and the argon gas was replaced by vacuum three times. Nitrogen and 5% hydrogen were introduced, and a pyrolysis reaction was carried out at a heating rate of 2°C / min. The temperature was raised to 1200°C and kept for 2 hours, and then cooled to room temperature to obtain inorganic fibers.

[0101] (5) placing the inorganic fiber in a high-temperature graphite furnace, evacuating and replacing argon gas three times, sintering at a high temperature of 1950° C. at a heating rate of 5° C. / min for 0.1 h, and cooling to room temperature to obtain the rare earth element-doped multiphase continuous silicon carbide ceramic fiber.

[0102] The composition and structure of the inorganic fiber obtained in step (4) of Example 2 and the rare earth element doped multiphase continuous silicon carbide ceramic fiber in step (5) were tested. The oxygen content of the inorganic fiber was 4.5% and the oxygen content of the ceramic fiber was 0.3wt% as measured by a nitrogen oxygen analyzer. The carbon content of the ceramic fiber was 30.0wt% as measured by a carbon sulfur analyzer. The element contents of Ti, B, Y, and Yb in the fiber were 1.4wt%, 0.9wt%, 0.8wt%, and 0.7wt%, respectively, as measured by inductively coupled plasma emission spectroscopy.

[0103] Example 3

[0104] This embodiment provides a method for preparing rare earth element doped multi-phase continuous silicon carbide ceramic fibers, the preparation method comprising:

[0105] (1) Polycarbosilane with a softening point of 80°C, hafnium dichloride, yttrium heptanedione, ytterbium heptanedione and trichloroborazine are placed in an autoclave in a mass ratio of 100:5:4:2:5, the temperature is raised to 380°C, the pressure is raised to 3.5 MPa, and the reaction is carried out at high temperature and high pressure for 10 hours, then the temperature is lowered to room temperature, the prepared precursor is dissolved in xylene, filtered, and then distilled under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements.

[0106] (2) The prepared polymetallic borocarbosilane ceramic precursor containing rare earth elements was added into a spinning tank and kept at 350°C for 4 hours for degassing treatment. The temperature was then lowered to 300°C and the pressure was 0.1 MPa for melt spinning to prepare fiber precursors with an average diameter of 15 μm.

[0107] (3) The fiber precursor was placed in a tubular furnace, and the vacuum was evacuated to replace the nitrogen three times. Synthetic air was introduced at a flow rate of 1 L / min, and the temperature was increased to 230°C at a heating rate of 2.5°C / min. The temperature was kept for 4 h and then cooled to room temperature to obtain cross-linked fibers.

[0108] (4) The cross-linked fibers were placed in a tubular furnace, and the argon gas was replaced by vacuum three times. The pyrolysis reaction was carried out at a heating rate of 2.5°C / min. The temperature was raised to 1100°C and kept for 2 hours, and then cooled to room temperature to obtain inorganic fibers.

[0109] (5) placing the inorganic fiber in a high-temperature graphite furnace, evacuating and replacing argon gas three times, sintering at a high temperature of 1850° C. at a heating rate of 5° C. / min for 1.5 h, and cooling to room temperature to obtain the rare earth element-doped multiphase continuous silicon carbide ceramic fiber.

[0110] The composition and structure of the inorganic fiber obtained in step (4) of Example 3 and the rare earth element doped multiphase continuous silicon carbide ceramic fiber in step (5) were tested. The oxygen content of the inorganic fiber was 8.5% and the oxygen content of the ceramic fiber was 0.2wt% as measured by a nitrogen oxygen analyzer. The carbon content of the ceramic fiber was 30.5wt% as measured by a carbon sulfur analyzer. The element contents of Hf, B, Y, and Yb in the fiber were 1.1wt%, 0.7wt%, 0.8wt%, and 0.7wt%, respectively, as measured by inductively coupled plasma emission spectroscopy.

[0111] Example 4

[0112] This embodiment provides a method for preparing rare earth element doped multi-phase continuous silicon carbide ceramic fiber, the preparation method comprising:

[0113] (1) Polycarbosilane with a softening point of 120°C, zirconocene dichloride, yttrium heptanedione and perhydroborazine are placed in an autoclave at a mass ratio of 100:10:1:5, the temperature is raised to 360°C, the pressure is raised to 3.0 MPa, and the high temperature and high pressure reaction is carried out for 6 hours. The temperature is then lowered to room temperature, and the prepared precursor is dissolved and filtered with xylene, and then distilled under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements.

[0114] (2) The prepared rare earth element-containing polymetallic borocarbosilane ceramic precursor was added to a spinning tank, kept at 350°C for 3 hours for degassing, then the temperature was lowered to 330°C and the pressure was 0.2 MPa for melt spinning to prepare fiber precursors with an average diameter of 17 μm. (3) The fiber precursors were placed in a tubular furnace, vacuumed and replaced with nitrogen three times, synthetic air was introduced at a flow rate of 1 L / min, the temperature was increased to 220°C at a heating rate of 1.5°C / min, kept at this temperature for 4 hours, and then cooled to room temperature to obtain cross-linked fibers.

[0115] (4) The cross-linked fibers were placed in a tubular furnace, and the argon gas was replaced by vacuum three times. The pyrolysis reaction was carried out at a heating rate of 2°C / min. The temperature was raised to 1300°C and kept for 1 hour, and then cooled to room temperature to obtain inorganic fibers.

[0116] (5) placing the inorganic fiber in a high-temperature graphite furnace, evacuating and replacing argon gas three times, sintering at a high temperature of 1900° C. at a heating rate of 5° C. / min for 0.5 h, and cooling to room temperature to obtain the rare earth element-doped multiphase continuous silicon carbide ceramic fiber.

[0117] The composition and structure of the rare earth element doped composite continuous silicon carbide ceramic fiber obtained in step (5) of Example 4 were tested. The oxygen content of the ceramic fiber was measured by a nitrogen oxygen analyzer to be 0.2wt%, the carbon content in the fiber was measured by a carbon sulfur analyzer to be 29.9wt%, and the element contents of Zr, B, and Y in the fiber were measured by inductively coupled plasma emission spectroscopy to be 1.5wt%, 1.6wt%, and 0.2wt%, respectively.

[0118] The X-ray spectrum scanning image of the rare earth element doped multiphase continuous silicon carbide ceramic fiber obtained in Example 4 is as follows: Figure 3 As shown, the energy spectrum data show that the fiber does contain Si, C, Zr, Y, B, and O elements, and the above elements are evenly distributed in the fiber without obvious enrichment or segregation.

[0119] Example 5

[0120] This embodiment provides a method for preparing rare earth element doped multi-phase continuous silicon carbide ceramic fiber, the preparation method comprising:

[0121] (1) Polycarbosilane with a softening point of 100°C, zirconocene dichloride, ytterbium heptanedione and trichloroborazine are placed in an autoclave at a mass ratio of 100:5:2:5, the temperature is raised to 360°C, the pressure is raised to 5 MPa, and the reaction is carried out at high temperature and high pressure for 8 hours. The temperature is then lowered to room temperature, and the prepared precursor is dissolved and filtered with xylene, followed by vacuum distillation to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements.

[0122] (2) The prepared polymetallic borocarbosilane ceramic precursor containing rare earth elements was added into a spinning tank and degassed at 360°C for 4 hours. The temperature was then lowered to 310°C and the pressure was 0.4 MPa for melt spinning to prepare fiber precursors with an average diameter of 20 μm.

[0123] (3) The fiber precursor was placed in a tubular furnace, and the vacuum was evacuated to replace the nitrogen three times. Synthetic air was introduced at a flow rate of 1 L / min, and the temperature was increased to 240°C at a heating rate of 0.5°C / min. The temperature was kept for 2 h and then cooled to room temperature to obtain cross-linked fibers.

[0124] (4) The cross-linked fibers were placed in a tubular furnace, and the argon gas was replaced by vacuum for three times. The pyrolysis reaction was carried out at a heating rate of 2°C / min. The temperature was raised to 1200°C and kept for 1 hour, and then cooled to room temperature to obtain inorganic fibers.

[0125] (5) The inorganic fiber is placed in a high-temperature graphite furnace, evacuated and replaced with argon three times, and sintered at a high temperature of 1850°C at a heating rate of 5°C / min for 1 hour, and then cooled to room temperature to obtain rare earth element-doped composite continuous silicon carbide ceramic fiber.

[0126] The composition and structure of the rare earth element doped multiphase continuous silicon carbide ceramic fiber obtained in Example 5 were tested. The oxygen content of the ceramic fiber was measured to be 0.3wt% by a nitrogen and oxygen analyzer, the carbon content in the fiber was measured to be 30.1wt% by a carbon and sulfur analyzer, and the element contents of Zr, B, and Yb in the fiber were measured to be 0.7wt%, 1.8wt%, and 0.7wt%, respectively, by inductively coupled plasma emission spectroscopy.

[0127] The X-ray spectrum scanning image of the rare earth element doped multiphase continuous silicon carbide ceramic fiber obtained in Example 5 is as follows: Figure 4 As shown, the energy spectrum data show that the fiber does contain Si, C, Zr, Yb, B, and O elements, and the above elements are evenly distributed in the fiber without obvious enrichment or segregation.

[0128] Example 6

[0129] This embodiment provides a rare earth element doped multiphase continuous silicon carbide ceramic fiber, which differs from Embodiment 1 only in that, when preparing the rare earth element doped multiphase continuous silicon carbide ceramic fiber, the transformation point temperature of the polycarbosilane in step (1) is 200°C, and the other steps remain unchanged.

[0130] Example 7

[0131] This embodiment provides a rare earth element doped multiphase continuous silicon carbide ceramic fiber, which is different from Embodiment 1 only in that when preparing the rare earth element doped multiphase continuous silicon carbide ceramic fiber, the temperature of the high temperature and high pressure reaction in step (1) is 220°C.

[0132] Example 8

[0133] This embodiment provides a rare earth element doped multiphase continuous silicon carbide ceramic fiber, which is different from Embodiment 1 only in that when preparing the rare earth element doped multiphase continuous silicon carbide ceramic fiber, the temperature of the high temperature and high pressure reaction in step (1) is 450°C.

[0134] Example 9

[0135] This embodiment provides a rare earth element doped multiphase continuous silicon carbide ceramic fiber, which differs from Embodiment 5 only in that, when preparing the rare earth element doped multiphase continuous silicon carbide ceramic fiber, the mass ratio of polycarbosilane, zirconocene dichloride, ytterbium heptanedione and trichloroboroazine in step (1) is changed to 100:5:0.1:5.

[0136] Example 10

[0137] This embodiment provides a rare earth element doped multi-phase continuous silicon carbide ceramic fiber, which is different from Embodiment 5 only in that, when preparing the rare earth element doped multi-phase continuous silicon carbide ceramic fiber, the mass ratio of polycarbosilane, zirconocene dichloride, ytterbium heptanedione and trichloroboroazine in step (1) is changed to 100:5:20:5.

[0138] Comparative Example 1

[0139] This comparative example provides a method for preparing metal boride-doped continuous silicon carbide ceramic fibers, which differs from Example 1 only in that no rare earth compound is added in step (1), and the mass of the reduced rare earth compound is distributed to polycarbosilane, dichlorozirconocene and trichloroborazine in proportion, while the other steps remain unchanged.

[0140] The microstructure of the continuous silicon carbide ceramic fiber prepared in this comparative example is as follows Figure 5 As shown, the fiber is in an obvious crystalline state, the structure is loose near the fiber core, and obvious defects such as holes are observed.

[0141] Comparative Example 2

[0142] This comparative example provides a method for preparing rare earth element doped multiphase continuous silicon carbide ceramic fiber, which differs from Example 1 only in that trichloroborazine is not added in step (1), and the reduced mass of trichloroborazine is distributed to polycarbosilane, zirconocene dichloride, yttrium heptanedione and ytterbium heptanedione in proportion, and the other steps remain unchanged.

[0143] Comparative Example 3

[0144] This comparative example provides a rare earth element doped multiphase continuous silicon carbide ceramic fiber, which is different from Example 1 only in that, when preparing the rare earth element doped multiphase continuous silicon carbide ceramic fiber, step (2) adopts electron beam crosslinking, and the specific operation of step (2) is: putting the raw silk fiber into an electron beam irradiation furnace, evacuating and replacing the gas with high-purity N2, introducing BCl3 / N2 mixed gas, wherein the volume concentration of BCl3 gas is 1-10%, and performing infusibility treatment on the raw silk fiber under electron beam excitation. The other steps remain unchanged.

[0145] Test method:

[0146] (1) Test method for single fiber strength: The test method is based on (GB / T 34520.5-2017) Continuous silicon carbide fiber test method Part 5: Single fiber tensile properties) and the test instrument is a 5944 universal material testing machine produced by Instron, USA. The test method is carried out in the following steps:

[0147] 1) Separate the fiber samples to be tested into bundles and bond them to a paper frame with a spacing of 25 mm;

[0148] 2) Turn on the tensile tester, set the test parameters, clamp the paper frame with the upper and lower clamps, cut the paper frame, and start the test. Select 25 groups of valid test result data (referring to the data where the test breaking point is located near the center of the fiber near the paper frame when the fiber is not bent), take the values ​​according to the test order, and calculate the CV value.

[0149] (2) Testing method of Young's modulus: Select two points on the straight line segment of the mechanical property test curve, input the fiber diameter, and obtain the Young's modulus of a single fiber.

[0150] (3) Test method for fiber strength: Read the maximum tensile force on the mechanical property test curve, input the fiber diameter, and obtain the tensile strength of a single fiber.

[0151] Table 1

[0152]

[0153]

[0154] The test results show that:

[0155] (1) It can be seen from Examples 1-5 that the present invention improves the sintering performance inside the fiber, reduces the free carbon content inside the fiber, and optimizes the grain boundary composition and structure of the silicon carbide ceramic fiber by introducing heterogeneous metal elements, rare earth elements and boron elements in combination with air crosslinking. Compared with the existing silicon carbide fibers, the temperature resistance, oxidation resistance and creep resistance of the rare earth-doped metal boride-containing composite silicon carbide ceramic fibers are improved.

[0156] (2) By comparing Example 1 with Example 6, it can be seen that the present invention uses polycarbosilane with a low softening point as a raw material, which has the advantages of continuous fiber and high strength. This is different from the prior art which generally uses polycarbosilane with a softening point temperature higher than 150°C as a raw material. The high conversion point will cause the molecular weight of the synthesized precursor to be too high, affecting the spinning performance, and ultimately failing to obtain continuous SiC fibers with good mechanical properties.

[0157] (3) By comparing Example 1 with Examples 7-8, it can be seen that the present invention further controls the temperature of the high temperature and high pressure reaction to be 150-400°C, which is lower than the reaction temperature in the prior art. If the reaction temperature is too high, it will cause excessive cross-linking reaction of the raw material molecules to generate a ceramic precursor with a molecular weight that is too large and has poor spinnability, thereby resulting in poor fiber continuity and mechanical properties. If the reaction temperature is too low, it will reduce the degree of reaction and the utilization rate of the raw materials. At the same time, the content of the introduced metal elements and rare earth elements is too low, and the effect of improving the fiber performance is not obvious.

[0158] (4) By comparing Example 1 with Examples 9-10, it can be seen that the present invention further controls the ratio of low softening point polycarbosilane, metallocene compound, rare earth compound and boron-containing compound to adjust the element content of the precursor, so that the content of metal elements in the precursor is 0.1-5wt%, the content of rare earth element Y is 0.1-1wt%, the content of rare earth element Yb is 0.1-1wt%, and the content of element B is 0.1-4.0wt%.

[0159] (5) It can be seen from Example 1 and Comparative Example 1 that the present invention, by introducing rare earth elements, can, on the one hand, promote sintering and improve the sintering performance of the fiber, especially the fiber core; on the other hand, it can also stabilize the MO2 phase and improve the high-temperature oxidation resistance of the fiber. At the same time, the addition of rare earth cations (RE 3+ ), which can increase the viscosity of SiO2 glass and further enhance the oxidation resistance of SiC ceramics.

[0160] (6) It can be seen from Example 1 and Comparative Example 2 that the present invention helps to optimize the grain boundary structure of silicon carbide fibers by adding a high melting point and high thermal stability ceramic phase MB2 (M = Ti, Zr, Hf) at the SiC grain boundaries of silicon carbide fibers, effectively inhibiting the grain growth of silicon carbide and the sliding of silicon carbide grains along the grain boundaries, thereby improving the temperature resistance and high-temperature creep resistance of silicon carbide fibers.

[0161] (6) It can be seen from Example 1 and Comparative Example 3 that the present invention, by adopting air crosslinking in the infusible stage of the fiber, not only avoids the use of expensive electron beam crosslinking, thereby reducing the preparation cost of the fiber, but also avoids the use of nitrogen oxide atmosphere crosslinking, thereby reducing corrosion to equipment and environmental impact, and more importantly, significantly improves the strength and Young's modulus of the silicon carbide ceramic fiber, thereby obtaining excellent mechanical properties.

[0162] In summary, the present invention improves the sintering performance inside the fiber, reduces the free carbon content inside the fiber, and optimizes the grain boundary composition and structure of the silicon carbide ceramic fiber by introducing heterogeneous metal elements, rare earth elements and boron elements during the precursor synthesis process and combining air crosslinking. Compared with the existing silicon carbide fibers, the preparation cost is low, and the prepared rare earth-doped metal boride-containing composite phase silicon carbide ceramic fiber has excellent mechanical properties, high temperature resistance and oxidation resistance.

[0163] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing rare earth element doped multiphase continuous silicon carbide ceramic fiber, characterized in that: The preparation method comprises: (1) mixing polycarbosilane, a metallocene compound, a rare earth compound and a boron-containing compound, reacting the mixture under high temperature and high pressure to obtain an intermediate product, and dissolving, filtering and distilling the intermediate product to obtain a polymetallic borocarbosilane ceramic precursor containing a rare earth element; (2) preparing fiber precursors by melt spinning the rare earth element-containing polymetallic borocarbosilane ceramic precursor described in step (1); (3) cross-linking the fiber precursors described in step (2) in a synthetic air atmosphere to prepare cross-linked fibers; (4) In an inert atmosphere and / or a reducing atmosphere, heating and pyrolyzing the crosslinked fibers in step (3) to obtain Si-MCOB-RE inorganic fibers, wherein M represents a metal element and RE represents a rare earth element; (5) Under an inert atmosphere, sintering the Si-MCOB-RE inorganic fiber in step (4) at a high temperature to obtain the rare earth element doped multiphase continuous silicon carbide ceramic fiber.

2. The preparation method according to claim 1, characterized in that: The structural formula of the polycarbosilane in step (1) is: Wherein, m is an integer equal to or greater than 3, and n is an integer equal to or greater than 0; Preferably, the softening point temperature of the polycarbosilane is 70-150°C; Preferably, the metallocene compound includes any one of dichlorotitanium, dichlorozirconium or dichlorohafnium, or a combination of at least two thereof; Preferably, the rare earth compound comprises any one or a combination of at least two of acetylacetone compounds, isopropanol compounds, and heptanedione compounds of rare earth elements; Preferably, the boron-containing compound includes any one of borane, boron trichloride, and cycloborazine, or a combination of at least two thereof; Preferably, the structural formula of the borazine is: Wherein, m is an integer equal to or greater than 1, and R is at least one of CH3, H or Cl.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polycarbosilane, the metallocene compound, the rare earth compound and the boron-containing compound in step (1) is (100-120):(5-15):(1-6):(5-10); Preferably, the temperature of the high temperature and high pressure reaction is 250-400°C; Preferably, the pressure of the high temperature and high pressure reaction is 1.0-5.0 MPa; Preferably, the high temperature and high pressure reaction time is 4-12 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The melt spinning step in step (2) specifically comprises: adding a polymetallic borocarbosilane ceramic precursor containing rare earth elements into a spinning tank, and performing melt spinning after high-temperature degassing and cooling to prepare fiber precursors; Preferably, the high temperature degassing temperature is 320-370°C; Preferably, the high temperature degassing time is 2-4h; Preferably, the melt spinning temperature is 90-130° C. higher than the softening point of the polymetallic borocarbosilane ceramic precursor; Preferably, the melt spinning temperature is 290-340°C; Preferably, the pressure during melt spinning is 0.05-0.5 MPa; Preferably, the diameter of the fiber filament is 12-20 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the cross-linking reaction in step (3) is 160-250°C; Preferably, the heating rate of the cross-linking reaction is 0.5-5°C / min; Preferably, the insulation time of the cross-linking reaction is 0.5-10h.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the pyrolysis in step (4) is 1000-1300°C; Preferably, the heating rate of the heating pyrolysis is 0.5-5°C / min; Preferably, the heating and pyrolysis time is 0.5-3h; Preferably, the inert gas comprises high-purity nitrogen or high-purity argon; Preferably, the reducing atmosphere comprises a mixture of nitrogen and hydrogen with a concentration of 2-10%; Preferably, the hydrogen mixed gas is a mixed gas of nitrogen and hydrogen with a mass fraction of 0.1-50%.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The high temperature sintering temperature in step (5) is 1800-1950°C; Preferably, the high temperature sintering time is 0.1-3h; Preferably, the inert gas comprises high-purity argon.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) adding polycarbosilane, metallocene compound, rare earth compound and boron-containing compound into a high-pressure reactor in a mass ratio of (100-120):(5-15):(1-6):(5-10), carrying out a high-temperature and high-pressure reaction for 4-12 hours at a temperature of 250-400° C. and a pressure of 1.0-5.0 MPa to obtain an intermediate product, dissolving the intermediate product in toluene or xylene, filtering and distilling under reduced pressure to obtain a polymetallic borocarbosilane ceramic precursor containing rare earth elements; (2) adding the rare earth element-containing polymetallic borocarbosilane ceramic precursor described in step (1) into a spinning tank, maintaining the temperature at 320-370° C. for 2-4 h for degassing, then cooling to 290-340° C., and performing melt spinning at a pressure of 0.05-0.5 MPa to prepare fiber precursors with a diameter of 12-20 μm; (3) heating the fiber precursor described in step (2) to 160-250° C. at a heating rate of 0.5-5° C. / min in a synthetic air atmosphere and keeping the temperature for 0.5-10 h to prepare a cross-linked fiber; (4) pyrolyzing the crosslinked fiber in step (3) in an atmosphere of high-purity nitrogen or high-purity argon or a mixture of nitrogen and 2-10% hydrogen at a heating rate of 0.5-5°C / min to 1000-1300°C and keeping the temperature for 0.5-3h to obtain Si-MCOB-RE inorganic fiber; (5) Sintering the Si-MCOB-RE inorganic fiber in step (4) at a high temperature of 1800-1950° C. for 0.1-3 h in a high-purity argon atmosphere to obtain the rare earth element doped multiphase continuous silicon carbide ceramic fiber.

9. A rare earth element doped multiphase continuous silicon carbide ceramic fiber, characterized in that: The rare earth element doped multiphase continuous silicon carbide ceramic fiber is prepared according to the preparation method according to any one of claims 1-8.

10. The rare earth element doped multiphase continuous silicon carbide ceramic fiber according to claim 9, characterized in that: The rare earth element doped multiphase continuous silicon carbide ceramic fiber has a single filament strength of 1.8-3.5 GPa and a Young's modulus of 350-410 GPa.

Citation Information

Patent Citations

  • Composite ceramic fiber and preparation method thereof

    CN104233512A

  • Boride-containing silicon carbide composite ceramic fiber and preparation method thereof

    CN114560704A

  • Preparation method of rare earth doped high-performance continuous silicon carbide fiber

    CN116103787A

  • Modified SiBCN ceramic composite material as well as preparation method and application thereof

    CN117185819A

  • Yttrium-aluminum-doped boron nitride fiber and preparation method thereof

    CN118531528A

Cited By

  • Hollow silicon carbide ceramic fiber as well as preparation method and application thereof

    CN120738801A

  • CVD growth type high-temperature-resistant silicon carbide and preparation method thereof

    CN121361799A